Trade, Foreign Direct Investment, and International Technology Transfer : A Survey - Saggi, Kamal (World Bank, 2013)
What role does trade play in international technology transfer? Do technologies introduced by multinational firms diffuse to local firms? What kinds of policies have proved successful in encouraging technology absorption from abroad and why? Using these questions as motivation, this article surveys the recent trade literature on international technology transfer, paying particular attention to the role of foreign direct investment. The literature argues that trade necessarily encourages growth only if knowledge spillovers are international in scope. Empirical evidence on the scope of knowledge spillovers (national versus international) is ambiguous. Several recent empirical plant-level studies have questioned earlier studies that argued that foreign direct investment has a positive impact on the productivity of local firms. Yet at the aggregate level, evidence supports the view that foreign direct investment has a positive effect on economic growth in the host country.